Dietary cholesterol and cardiovascular disease: a systematic review and meta-analysis - Berger, Samantha; Raman, Gowri; Vishwanathan, Rohini; Jacques, Paul F; Johnson, Elizabeth J (The American journal of clinical nutrition, 2015)
Dietary cholesterol has been suggested to increase the risk of cardiovascular disease (CVD), which has led to US recommendations to reduce cholesterol intake. The authors examine the effects of dietary cholesterol on CVD risk in healthy adults by using systematic review and meta-analysis. MEDLINE, Cochrane Central, and Commonwealth Agricultural Bureau Abstracts databases were searched through December 2013 for prospective studies that quantified dietary cholesterol. Investigators independently screened citations and verified extracted data on study and participant characteristics, outcomes, and quality. Random-effect models meta-analysis was used when at least 3 studies reported the same CVD outcome. Forty studies (17 cohorts in 19 publications with 361,923 subjects and 19 trials in 21 publications with 632 subjects) published between 1979 and 2013 were eligible for review. Dietary cholesterol was not statistically significantly associated with any coronary artery disease (4 cohorts; no summary RR), ischemic stroke (4 cohorts; summary RR: 1.13; 95% CI: 0.99, 1.28), or hemorrhagic stroke (3 cohorts; summary RR: 1.09; 95% CI: 0.79, 1.50). Dietary cholesterol statistically significantly increased both serum total cholesterol (17 trials; net change: 11.2 mg/dL; 95% CI: 6.4, 15.9) and low-density lipoprotein (LDL) cholesterol (14 trials; net change: 6.7 mg/dL; 95% CI: 1.7, 11.7 mg/dL). Increases in LDL cholesterol were no longer statistically significant when intervention doses exceeded 900 mg/d. Dietary cholesterol also statistically significantly increased serum high-density lipoprotein cholesterol (13 trials; net change: 3.2 mg/dL; 95% CI: 0.9, 9.7 mg/dL) and the LDL to high-density lipoprotein ratio (5 trials; net change: 0.2; 95% CI: 0.0, 0.3). Dietary cholesterol did not statistically significantly change serum triglycerides or very-low-density lipoprotein concentrations. Reviewed studies were heterogeneous and lacked the methodologic rigor to draw any conclusions regarding the effects of dietary cholesterol on CVD risk. Carefully adjusted and well-conducted cohort studies would be useful to identify the relative effects of dietary cholesterol on CVD risk.